Democratic Republic of the Congo : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
As envisaged in its interim Poverty Reduction Strategy Paper, the country has moved from the stabilization phase to the reconstruction phase, and the authorities have continued to make major progress in consolidating the peace process. The important tasks will be to preserve macroeconomic stability, deepen structural reforms, promote an environment that is conducive to private-sector led growth, and combat widespread poverty. The policies of the Central Bank of Congo are successful in controlling inflation. It is also important to continue the reform of the mining sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet